A silk fibroin based green nano-filter for air filtration. Issue 15 (20th February 2018) - Gao, Xiaochao; Gou, Jing; Zhang, Ling; Duan, Shasha; Li, Chunzhong
Abstract : This paper reports the fabrication of a silk fibroin nanofiber air filter via a green electrospinning method. Abstract : Fibrous air filters fabricated by electrospinning have proved to be an effective approach among the various strategies for PM2.5 removal. However, in the electrospinning process, the large amounts of toxic organic solvents usually evaporate into the atmosphere and disposing of these used polymer-based air filters would leave further pollution in the environment. Here, we report on the fabrication of a silk fibroin based nanofiber air filter with robust filtration performance via a green electrospinning process. Silk worm cocoons were degummed and dialyzed against water to form the silk fibroin solution and then the silk fibroin nanofiber membranes were fabricated by electrospinning with the help of polyethylene oxide. Moreover, special attention was paid to the morphological evolution of the pollutants captured by the nanofiber nets during the filtration process. It was discovered that the inherent properties of silk fibroin play a key role in improving the filtration performance. Benefiting from the richness of functional groups, the resultant silk fibroin fibrous membranes exhibited a high filtration efficiency of 99.99% with a relatively low air resistance of only 75 Pa, leading to an obvious higher quality factor. Due to the biodegradability of silk fibroin, the membranes are disposable after use. We believe that the methodology and results presented here will not only provide a novel perspective for air filtration, but also pave the way for producing a safe and clean air filtration system.